Implementasi Teori Four Aspects of Language Learning dalam Pembelajaran Bahasa Arab bagi Siswa Berkebutuhan Khusus - Hasan, Laili Mas Ulliyah; Vetiana, Gautama Veri; Salma, Kunti Nadiyah (Journal of Arabic Language Studies and Teaching, 2025)
This study examines how MTs Wachid Hasyim Surabaya, an inclusive school, apply William Francis Mackey's Four Aspects of Language Learning Theory to teach Arabic to special needs pupils in Grade 8. The study focuses on the application of phonetics, grammar, semantics, and graphology to improve students' learning of the Arabic language.  A qualitative approach is used to analyze teaching methods, learning materials, and student progress in inclusive classroom settings. Findings suggest that incorporating phonetic exercises helps students, particularly those with speech impairments, enhance their pronunciation. Grammar instruction is adapted to incorporate visual and interactive media, supporting students with ADHD and those who are slow learners. Semantic teaching is reinforced through contextual storytelling and role-playing, making it easier for students to grasp meaning. Graphology-based techniques can help children with learning disabilities improve their writing and reading skills. The study highlights the importance of multimodal and adaptive teaching methods in meeting a range of learning needs. This study provides suggestions for enhancing teaching strategies based on Mackey's framework and facilitates the development of inclusive Arabic language teaching models.